Monopolistic Competition, Optimum Product Diversity, and International Trade - The Role of Factor Endowment and Factor Intensities - Sugata Marjit; Biswajit Mandal (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this paper we revisit the influential theory of monopolistic competition and optimum product variety as developed by Dixit and Stiglitz (1977) with applications in international trade by Krugman (1979,1980), by modeling fixed and variable costs of production in terms of underlying use of skilled and unskilled labor in a single good model. This is different from earlier work on multi sector variant of Krugman cum Heckscher-Ohlin-Samuelson model such as Helpman (1981) and others. In our structure factor endowment and factor intensities determine both number of varieties and output per variety in a closed economy mimicking the features of Heckscher-Ohlin-Samuelson model. Differences in factor endowments across countries determine the pattern of trade between varieties and output per variety, which is indeterminate in a standard single good Dixit-Stiglitz-Krugman model. Later we reflect on wage inequality and unemployment providing some interesting results.
Keywords: D43; F10; J31; F24; 330; monopolistic competition; trade; wage inequality; unemployment